Analisa Perbandingan Daya Keluaran Panel Surya Tipe Monokristalin 50wp Yang Dirangakai Seri Dan Paralel Pada Instalasi Plts Off-Grid - Hamid Abdillah; Tri Winahyu Hariyadi; Dita Amalia (Politeknik Caltex Riau, 2022)
Indonesia is a country that has the potential to develop solar energy. In Indonesia, there is a tool that functions to convert solar energy into electrical energy called photovoltaic. The research uses monocrystalline solar panels because they are the most efficient and produce the highest electrical power per unit area. This research aims to analyze the comparison of solar cells, which are arranged in series and parallel to the output power. Researchers made direct observations of the field and studied after getting some data from the measurement results. Then conclude from the results of this observation. Sampling was researched on the output of solar panels located at BBPLK Serang. The method used is the comparative analysis method, by comparing the differences and similarities of an event. The voltage and currently issued by a series of solar panels is 35.77V and 3.18A. The results of the voltage and presently published by a parallel series of solar panels are 17,69V and 6.38 A. The power is produced by a series circuit of 113.75atts and a parallel circuit of 112,86Watts. From the output power results, the series circuit is 0,89Watts greater than the parallel circuit. Judging from the advantages and disadvantages, it is better to install PLTS Off-Grid installations in parallel. If damage to damaged components is damaged, it will be easier to inspect, and several other panels can still function properly, so electricity continues to flow.